Manajemen Pendidikan Karakter - Sumaryatihttp://e-journal.metrouniv.ac.i, Sumaryati (Institut Agama Islam Negeri (IAIN) Metro, 2016)
This paper describes managed character education. Where, character education is the cultivation of the values that are so important that must be applied in everyday life, which started from within the family, school, community and country so as to provide a positive contribution to the environment. Character education developed through the stage of knowledge (knowing), implementation (acting), and habits (habit). Character education is not limited to knowledge alone, but reach out to the area of emotions and habits yourself. So it required three components of good character, namely moral feeling, knowing morals, and morals acting. From this then needed a good management and synergistic between the various components of education involved both the nature of formal, non-formal, and informal, whether in the family, schools, neighbourhoods, as well as the wider community.